2019
DOI: 10.3389/fimmu.2019.00892
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Unravel Hidradenitis Suppurativa Etiopathogenesis

Abstract: Hidradenitis suppurativa/acne inversa (HS) is a chronic inflammatory disease involving hair follicles that presents with painful nodules, abscesses, fistulae, and hypertrophic scars, typically occurring in apocrine gland bearing skin. Establishing a diagnosis of HS may take up to 7 years after disease onset. HS severely impairs the quality of life of patients and its high frequency causes significant costs for health care system. HS patients have an increased risk of developing associated diseases, such as inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 100 publications
1
56
0
1
Order By: Relevance
“…The exact etiology of HS is yet not completely unraveled; however, both genetic and environmental factors are known to trigger the development of the disease. A recent article by Tricarico et al reported an exhaustive overview of the genes involved in HS susceptibility [ 93 ], highlighting that about 35% of HS patients present a family history of HS. Mutations in NCSTN , PSENEN and PSEN1 genes, respectively encoding for NCSTN, PSENEN and PSEN1, have been identified as the most common genetic variants involved in HS familial cases.…”
Section: Notch Signaling and Skin Diseasesmentioning
confidence: 99%
“…The exact etiology of HS is yet not completely unraveled; however, both genetic and environmental factors are known to trigger the development of the disease. A recent article by Tricarico et al reported an exhaustive overview of the genes involved in HS susceptibility [ 93 ], highlighting that about 35% of HS patients present a family history of HS. Mutations in NCSTN , PSENEN and PSEN1 genes, respectively encoding for NCSTN, PSENEN and PSEN1, have been identified as the most common genetic variants involved in HS familial cases.…”
Section: Notch Signaling and Skin Diseasesmentioning
confidence: 99%
“…In 2010, mutations in genes encoding γ-secretase subunits (NCSTN, PSENEN, and PSEN1) were reported in patients presenting with hidradenitis suppurativa (HS) (36). The essential subunit of the γ-secretase complex, an endoprotease complex, catalyzes the intramembrane cleavage of integral membrane proteins, such as Notch receptors, and amyloid-beta precursor protein (37). γ-Secretase deficiency could also regulate inflammation by processing important cytokine receptors such as IL-1β R1/R2 and IL-6R (37).…”
Section: Other Cutaneous Phenotypes Associated With Autoinflammation mentioning
confidence: 99%
“…The essential subunit of the γ-secretase complex, an endoprotease complex, catalyzes the intramembrane cleavage of integral membrane proteins, such as Notch receptors, and amyloid-beta precursor protein (37). γ-Secretase deficiency could also regulate inflammation by processing important cytokine receptors such as IL-1β R1/R2 and IL-6R (37). HS caused by mutations in genes encoding γ-secretase subunits was suggested to have features characteristic of an AiKD (9, 38).…”
Section: Other Cutaneous Phenotypes Associated With Autoinflammation mentioning
confidence: 99%
“…TARTIŞMA HS, geleneksel olarak ter bezlerinin bir hastalığı olarak görülse de, şu anki anlayış genetik olarak duyarlı bireylerde tekrarlayan mekanik stres nedeniyle oluşan foliküler epitel bozukluğudur. HS patogenezinde düzensiz immünitenin primer rolü olduğu ortaya konulmuştur (9). Birçok çalışma, lezyonlu deride interlökin (IL) -1 beta, TNF, IL-17 ve IL-10 pro ve anti-inflamatuar sitokinlerin yüksek seviyelerini göstermiştir (10).…”
Section: Introductionunclassified